Emerging Trends in Sustainable Building Materials: Technological Innovations, Enhanced Performance, and Future Directions - Saavedra-Flores, E; Avudaiappan-, S (Elsevier B.V., 2024)
This study rigorously assesses the latest advancements in sustainable building materials, focusing on their classification, innovative production technologies, and performance metrics. We categorize sustainable materials into natural substances, such as bamboo and hemp; recycled products, like crushed concrete and recycled plastics; and innovative composites, including fiber-reinforced polymers. We emphasize the application of advanced manufacturing techniques such as 3D printing and automated fabrication, which significantly boost efficiency and minimize waste in the construction industry. These materials are critically evaluated using standards such as ASTM for mechanical properties and ISO for environmental impacts, affirming their practical viability and durability. However, the adoption of these materials faces obstacles like high initial costs, technical integration challenges, and stringent regulatory frameworks. We provide specific examples, such as the economic impact of switching to bio-based composites and the technical adjustments required for incorporating recycled plastics into structural applications. Looking forward, this paper delves into prospects and research directions, highlighting the need for scalability and integration into conventional construction practices to fully harness the potential of these sustainable materials. This work underscores the vital role of sustainable materials in fostering environmentally friendly and resilient built environments, advocating for continued research and interdisciplinary collaboration to navigate existing challenges and achieve widespread implementation. © 2024